The road to recovery: Financial resilience and mental health in post-apartheid South Africa - Felix Essel-Gaisey; Michael Adu Okyere; Richmond Forson; Tsun-Feng Chiang (Elsevier, 2023)
Following the post-apartheid era in South Africa, global economic hardships and financial shocks have forced most households to endure various mental and psychological stresses.. This has hindered the achievement of Sustainable Development Goal 3 (SDG-3)-good health and wellbeing-prompting policymakers and academics to search for remedies to mitigate such stresses. Highlighting resilience as a means of improving wellbeing, this paper focuses on financial resilience and constructs an index using a multidimensional framework to investigate its association with mental health disorders. Using the South Africa National Income Dynamic Study alongside several robust estimation techniques, we uncover a negative association between financial resilience and mental health disorders among South Africans. More specifically, financial resilience is associated with an approximately 37% decrease in the occurrence of mental health disorders. The results also reveal disparities in the correlation between financial resilience and mental health disorders across different subgroups. Non-Whites (especially Blacks), urban dwellers, and male household heads are shown to most strongly experience the depression-reducing effect of financial resilience. This paper also shows that life satisfaction and household expenditure mediate the relationship between financial resilience and mental wellbeing. Toward the end of this paper, we discuss the implications of our results and offer some policy recommendations.